Legal Protection of Consumers in Online Business: A Criminal Law Perspective in Handling Fraud and Identity Theft - Marsela, Dian; Yudhistira, Yustian; Fawaid, Bahrul (LifeSciFi, 2024)
In the rapidly growing digital era, the phenomenon of fraud and identity theft in online business has become a significant challenge. In the face of this threat, legal protection of consumers plays an important role, especially in the context of a criminal law perspective. This research uses a qualitative approach with a literature study to explore these issues by taking into account the views of legal experts, government officials, consumer victims, and other stakeholders. Secondary data used included relevant laws, regulations, case studies, and academic literature. The results of this research discuss the complexities and challenges in criminal law enforcement related to fraud and identity theft in online businesses. The research emphasizes the importance of cross-sector collaboration and the development of best practices in enhancing consumer protection. The implications of these findings for law enforcement policy and practice are set out as recommendations for governments, law enforcement agencies, e-commerce companies and non-governmental organizations. This research provides an in-depth understanding of consumer protection issues in online business from a criminal law perspective and contributes to the overall improvement of the consumer protection system.